PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA NIAGA SUPERMARKET - BAIQ SOLATIYAH; AHMAD RAPSAN JANI (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to determine the effect of price and service quality on customer satisfaction at Niaga Supermarket. The data source used is primary data in the form of a questionnaire. The type and research approach used is a quantitative approach. The sampling technique uses a purposive sampling method. The data analysis techniques used are instrument testing, classical assumption testing, and hypothesis testing. Based on the results of the t test, partially the price variable has no effect on customer satisfaction with a calculated t of 1.311 < t table, namely 1.993 and a significance value of 0.194 > 0.05. In service quality, only the reliability and guarantee variables have an influence on customer satisfaction because they have a calculated t value of more than t table and a significance value less than alpha, while the variables of responsiveness, empathy and physical evidence have no influence on customer satisfaction because the calculated t value less than t table and the significance value is greater than alpha. And the results of the F test show that the calculated f value is greater than the f table or 19.77 > 2.23 and a significance value of 0.000 < 0.05 so it can be concluded that the independent variables simultaneously have an influence on customer satisfaction